Sustainability-Centric Green Human Resource Management: An Imperative for the Contemporary Era - Dilawar, Bilal; Imtiaz, Umer; Cheema, Shahan (Annals of Human and Social Sciences, 2023)
This research aims to explore the essence of "Green" and "Green Human Resource Management (HRM)," elucidating their significance in the context of sustainable development. Emerging from the ecological movement, Green HRM responds to environmental challenges. The 1972 UN Conference on Human Environment emphasized the need to protect and enhance the human environment. Green HRM integrates environmentally responsible practices into HR policies, symbolizing peace, growth, and vitality. Using a comprehensive approach, this research delves into Green HRM’s principles, advantages, and constraints. It explores how organizations align policies with sustainable practices, drawing on literature and real-world examples. Adopting Green HRM is imperative for organizations developing eco-friendly products, managing environmental initiatives, and contributing to long-term well-being. Organizations should prioritize integrating Green HRM practices, fostering a culture of sustainability to contribute to a greener future. In conclusion, this research underscores Green HRM’s significance, serving as a resource for students, researchers, and educators, cultivating understanding in sustainable HR practices.